Biochemical Dissection of the Natural Diversification of Microcystin Provides Lessons for Synthetic Biology of NRPS. Issue 4 (21st April 2016) - Meyer, Sabine; Kehr, Jan-Christoph; Mainz, Andi; Dehm, Daniel; Petras, Daniel; Süssmuth, Roderich D.; Dittmann, Elke
Summary: The cyanobacterial hepatotoxin microcystin is assembled at a non-ribosomal peptide synthetase (NRPS) complex. The enormous structural diversity of this peptide, which is also found in closely related strains, is the result of frequent recombination events and point mutations. Here, we have compared the in vitro activation profiles of related monospecific and multispecific modules that either strictly incorporate leucine or arginine or incorporate chemically diverse amino acids in parallel into microcystin. By analyzing di- and tri-domain proteins we have dissected the role of adenylation and condensation domains for substrate specificity. We have further analyzed the role of subdomains and provide evidence for an extended gatekeeping function for the condensation domains of multispecific modules. By reproducing natural point mutations, we could convert a monospecific module into a multispecific module. Our findings may inspire novel synthetic biology approaches and demonstrate how recombination platforms of NRPSs have developed in nature. Graphical Abstract: Highlights: Microcystin synthetases feature recombination-tolerant condensation domains Chemically distinct variants are produced by multispecific peptide synthetase modules C domains in multispecific modules exhibit an extended gatekeeping function Abstract : Meyer et al. have biochemically dissected the impact of recombination events and point mutations on the diversification of microcystin. Their findings shed new light on the importance of dynamic interactions of adenylation and condensation domains for the substrate activation by non-ribosomal peptide synthetase (NRPS) modules.